HUBUNGAN PEMBERIAN REWARD DENGAN MINAT BELAJAR SISWA DI SEKOLAH MTs DARUL ILMI KELAS VIII TAHUN AJARAN 2021/2022 - Rahmarani Akmal Hia; Eryanti Lisma (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the relationship between reward and interest in learning in class VIII MTs Darul Ilmi Batang Kuis. Based on the results of observations, it is known that during the learning process the teacher has given rewards but not optimally. This is rarely done because the teacher thinks that when students get good grades, it makes students happy. In fact, students also want their work to be recognized and appreciated so that they are more motivated to increase their interest in learning. The formulation of the problem in this study is "Is there a relationship between reward giving and interest in learning in class VIII MTs Darul Ilmi?". The purpose of this study was to determine the relationship between reward giving and interest in learning in class VIII MTs Darul Ilmi. This research was conducted using quantitative research methods. Based on the data and hypotheses, the reward variable has a relationship with the learning interest variable. It can be seen that the proposed hypothesis is accepted with a value of "r" product moment, which is 0.815. The data is assumed to be normally distributed and has a homogeneous variance so that based on the results of hypothesis testing related to the formulation of the problem using the PPM (Pearson product moment) correlation formula, the rxy price is 0.815 more greater than r table 0.374 ie 0.53 > 0.374, so it can be seen that the alternative hypothesis (Ha) in this study is accepted. This means that there is a relationship between rewards and student interest in learning, so it can be concluded that the theory states that "Factors that can influence the emergence of interest in learning in students are one of the social factors where someone is interested in high achievement in order to get high social status as well and get recognition or appreciation from the environment he is in” proved to be true